1996
DOI: 10.22358/jafs/69600/1996
|View full text |Cite
|
Sign up to set email alerts
|

The influence of molasses and yeast culture on the performance of growing bulls on grass silage-based diet

Abstract: ] in the concentrate mixture on feed intake, live weight gain and carcass characteristics of growing Ayrshire bulls were examined in a 3 x 2 factorial design. Twenty-eight animals with a mean initial hveweight (LW) of 268 kg were used. Molasses replaced a part of concentrate, which was based on a mixture (1:1) of barley and sugar beet pulp. Grass silage was offered ad libitum and the concentrate supplements at the rate of 100 g per LW°6 on air dry basis. YC (5 g day' 1 ) was top-dressed on the concentrate. Fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, both 4 and 8% molasses DM improved production when supplementing a 65% alfalfa silage diet. Huhtanen and Hissa (1996) reported depressed weight gain and feed efficiency when about 4 and 8% molasses DM were added to a grass silage diet fed to growing bulls. Lactose yield, which did not display a significant quadratic response, was lowest at the highest level of molasses feeding.…”
mentioning
confidence: 99%
“…However, both 4 and 8% molasses DM improved production when supplementing a 65% alfalfa silage diet. Huhtanen and Hissa (1996) reported depressed weight gain and feed efficiency when about 4 and 8% molasses DM were added to a grass silage diet fed to growing bulls. Lactose yield, which did not display a significant quadratic response, was lowest at the highest level of molasses feeding.…”
mentioning
confidence: 99%
“…However, the literature data dealing with the effect of M supple-mentation on EMPS and related traits are contradictory. Stokes et al (1991), Givens et al (1992) and Ordonez-Tercero et al (2003) confirmed a positive effect of M, while others reported no (Murphy et al, 1993) or even negative effect (Huhtanen and Hissa, 1996) of M inclusion in the GS diet.…”
Section: Introductionmentioning
confidence: 90%